The Validity, Reliability and Usability of the Studio Alterazioni Cutanee Stomali (SACS) and Ostomy Skin Tool (OST) Instruments for Classification of Peristomal Skin Disorders: A Systematic Review - Degol, Lien; Olaerts, Ine; Jacobs, Stijn; Sergeant, Gregory; Depaifve, Yves; Paque, Kristel; Milisen, Koen (Journal of wound, ostomy, and continence nursing, 2025)
The aim of this systematic review was to synthesize the published literature to determine the validity, reliability, and usability of the Studio Alterazioni Cutanee Stomali (SACS) and Ostomy Skin Tool (OST) instruments. Systematic literature review. We searched the following electronic databases: PubMed, CINAHL via EBSCO, Embase, and CENTRAL. The search was limited to studies published after 2005 and written in the English or Dutch languages. Inclusion criteria were adults (18 years or older) with any type of abdominal ostomy created for any medical indication. Elements were selected for inclusion when they examined or described at least one psychometric aspect regarding validity, reliability, or usability of the OST or SACS. The search retrieved 3077 records after removing duplicate elements. This systematic review is based on findings from four studies identifying two different psychometric properties. The Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN) Risk of Bias Checklist and the COSMIN Risk of Bias Tool were used to assess the methodological quality of the included studies. The modified GRADE-approach was used to evaluate the quality of evidence for outcomes reported in this systematic review. According to the COSMIN criteria, the overall assessment for reliability and content validity was variable or indeterminate. This results in a low quality of evidence regarding the assessment instruments SACS and OST. Based on these findings, we conclude that neither the SACS nor OST have been sufficiently evaluated to fully determine their validity, reliability and usability in the clinical setting. More research of peristomal skin assessment instruments SACS and OST is needed for further refining and validation before they can be introduced as a "gold standard" in practice among nurses, experts, and clinicians.